Struktur Anatomi Kayu Beberapa Jenis Buah-Buahan - Yulia Sandri; Tesri Maideliza; - Syamsuardi (Jurnal Biologi Universitas Andalas, 2013)
The aim of this study was to describe the anatomical structure and quality of wood from fruit plants. This study was conducted from December 2012 to February 2013. The woods of five fruits species in Padang namely Artocarpus integra (cempedak), Baccaurea motleyana (rambai), Mangifera caesia (binjai), Mangifera foetida (ambacang), and Mangifera odorata (kuweni) were analyzed. The character of vessels, parenchyma, and rays were analyzed by using permanent slide, and fibre dimension by maceration method. The results showed that all of woods in this study have the same type of porous namely difuse and soliter type. The smallest porous was detected at wood of B. motleyana among those species. The parenchyma and rays characters of A. integra and B. motleyana have apotracheal and uniseriate types while M. caesia, M. foetida, and M. odorata have paratracheal and multiseriate types. Wood of B. motleyana has the longest fibre, differed from woods of M. caesia and M. odorata with short fibres. Based on industrial woods that A. integra and B. motleyana were classified in II-III of strength, differed from woods of M. caesia, M. foetida and M. odorata were classified in III-IV of strength.Keywords : anatomical structure, permanent slide, fruits wood, wood quality.